Microcápsulas probióticas aplicadas à produção de salame tipo italiano - Silva, Pablo Teixeira da (2014)
The aim of this study was to develop probiotic microcapsules of Bifidobacterium animalis and Lactobacillus acidophilus evaluating the survival of the microencapsulated probiotics under simulated gastrointestinal conditions and availability during storage at different temperatures, with further application to the production of Italian salami evaluating their effects on the physicochemical, microbiological and sensory characteristics of salami. Survival assays were conducted to evaluate the resistance of the microencapsulated probiotic to simulated gastrointestinal conditions and availability during 120 days of storage at 4°C and 25 ° C, besides to morphological analysis of the microcapsules. The microcapsules showed spherical shape with relatively smooth and continuous surface without cracks, protecting the probiotics from simulated gastrointestinal conditions when compared to free probiotics, remained with greater viability after 120 days of storage at 4°C for both microorganisms. After probiotic microcapsules were added to the production of Italian salami, generating three treatments: T1 control and T2 and T3 with the addition of microcapsules of B. animalis and L. acidophilus, respectively. Analyzes of water activity, pH, moisture, weight loss, coliform at 45ºC, Staphylococcus coagulase positive and Salmonella spp. detection were realized and monitoring the microencapsulated probiotic cultures, all analyzes were conducted during 120 days; beyond sensory analysis of salami after 30 days and monthly up to 120 days. There were no significant difference (p>0,05) between the treatments in relation to physicochemical, microbiological and sensory analyses. The treatments T2 e T3 maintained counts of B. animalis and L. acidophilus above 6 log CFU.g-1 to 90 days. Therefore, the production of probiotic Italian salami is possible. However, it is suggested that probiotics salamis should be designed such that the microorganisms can maintain their availability until the end of the shelf life of the product, either by changing the structure of the microcapsule or increasing the microorganism initial number or reducing the shelf life of the product.